DEVELOPMENT OF A COMPUTER FEEDBACK TESTING SYSTEM FOR MEASURING TEACHER COMPETENCY: RESEARCH KNOWLEDGE FOR PROBLEM SOLVING AND LEARNER DEVELOPMENT OF STUDENTS OF THE THAILAND NATIONAL SPORTS UNIVERSITY - Noonoi, Rungsimaporn; Panyakham, Chokchai (Academic Journal of Thailand National Sports University, 2024)
The objectives of this research were to develop the measurement test of teacher competency: research knowledge for problem solving and learner development of students and to develop a computer feedback testing system for measuring teacher competency: research knowledge for problem solving and learner development of students of the Thailand National Sports University. This research development with the concept of two-parameter item response model. The researchers examined the quality of items with 365 students by a multi - stage sampling method and experimented the testing system with 83 students in their fourth year by purposive sampling. The instruments comprised a standard based evaluation scale and a satisfaction evaluation scale for a computer feedback testing system, there were 5 - point rating scales. Data were analyzed using frequency, percentage, mean, standard deviation, skewness, and kurtosis. The research finding was as follows, the development of measures of teacher competency: research knowledge for problem solving and learner development. The quality of the items for content validity, discriminant of item, the difficulty of item according to the criteria and the quality of the measurements was checked by determining the reliability of the entire items, the result was 0.82. and the development of a computer feedback testing system for measuring teacher competency: research knowledge for problem solving and learner development of students of the Thailand National Sports University. The assessment of the quality of the system with standards based evaluation was conducted, and the results showed that the quality of the system reached high levels ( = 4.19, S.D. = 66) and the assessment result of student satisfaction, the results showed that most students were satisfied with the system at the highest levels ( = 4.31, S.D. = 0.61).